Die Judasbrief: "n Simboliese universum in die gedrang - Joubert, S. J. (Hervormde teologiese studies, 1988)
The letter of Jude: A symbolic universe endangered The readers to whom Jude adresses his letter experience alienation from their symbolic universe because of their contact with certain people who hold a different interpretation of God. Within the letter's textworld Jude maintains his reader's symbolic universe by changing their image from that of a weak group to a strong group with a clearly defined status and role. He also presents their world as an ordered whole and as the only legitimate form of existence where God protects those who obey his commands and punishes those who place themselves outside the readers' symbolic universe through their conduct.